Catalyst‐Free Synthesis of O‐Heteroacenes by Ladderization of Fluorinated Oligophenylenes. (15th February 2021) - Feofanov, Mikhail; Akhmetov, Vladimir; Takayama, Ryo; Amsharov, Konstantin
Abstract: A novel catalyst‐free approach to benzoannulated oxygen‐containing heterocycles from fluorinated oligophenylenes is reported. Unlike existing methods, the presented reaction does not require an oxygen‐containing precursor and relies on an external oxygen source, potassium tert ‐butoxide, which serves as an O 2− synthon. The radical nature of the reaction facilitates nucleophilic substitution even in the presence of strong electron‐donating groups and enables de‐ tert ‐butylation required for the complete annulation. Also demonstrated is the applicability of the method to introduce five‐, six‐, and seven‐membered rings containing oxygen, whereas multiple annulations also open up a short synthetic path to ladder‐type O‐heteroacenes and oligodibenzofurans. Abstract : O‐heteroacenes are now available by a one‐step LOOP reaction by SET‐induced SN Ar‐radical de‐ tert ‐butylation‐SN Ar. t BuOK serves as a reliable oxygen atom source and O 2− synthon, enabling synthesis of dibenzofuran, benzoxanthenes, and benzooxepines, and a range of longer ladder‐type O‐heteroacenes from fluorinated oligophenylenes.